2000
DOI: 10.1002/1099-1646(200007/08)16:4<307::aid-rrr582>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic perturbation of lowland river channels and ecological response

Abstract: Certain lowland streams have experienced prehistorical and historical cycles of aggradation, occlusion, degradation, headward incision, and renewed aggradation. Historical cycles appear to be related to human activities. A case study is presented of the Yalobusha River in Mississippi with emphasis on the effects of blockage and removal on aquatic habitats and fish. The adjacent Skuna River, which was channelized and unblocked, was used in space for time substitution to infer effects of blockage removal on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
0
27
1
Order By: Relevance
“…Nonetheless, the overwhelming importance of hydrologic regime to structuring the fish community (Grossman et al, 1998) may mask the effects of more subtle habitat changes on fish assemblages in these incised streams. Metrics other than abundance, such as species composition-based metrics (Shields et al, 2000), functional group composition, and assemblage size/age structure (Schlosser, 1982;Shields & Knight, 2004) may be more appropriate for assessing assemblage changes resulting from changes in stream conditions. If long enough time series before and after a change are available, then the degree of variability in abundance, itself, may be a useful indicator of a shift along the continuum of 'colonizing' to 'stable' assemblages as habitat shifts along the harsh to benign continuum (Schlosser, 1982(Schlosser, , 1987.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the overwhelming importance of hydrologic regime to structuring the fish community (Grossman et al, 1998) may mask the effects of more subtle habitat changes on fish assemblages in these incised streams. Metrics other than abundance, such as species composition-based metrics (Shields et al, 2000), functional group composition, and assemblage size/age structure (Schlosser, 1982;Shields & Knight, 2004) may be more appropriate for assessing assemblage changes resulting from changes in stream conditions. If long enough time series before and after a change are available, then the degree of variability in abundance, itself, may be a useful indicator of a shift along the continuum of 'colonizing' to 'stable' assemblages as habitat shifts along the harsh to benign continuum (Schlosser, 1982(Schlosser, , 1987.…”
Section: Discussionmentioning
confidence: 99%
“…In regulated rivers, bedload is rarely transported past large dams, hence virtually eliminating the (volumetric) input term of the sediment budget from upstream (Vaithiyanathan et al, 1992). In these areas, sediment-starved flow may erode the channel bed and banks, producing channel incision, bed material coarsening, and gravel loss (Waldichuk, 1993;Gilvear and Bradley, 1997;Kondolf, 1997;Shields et al, 2000). Such changes typically result in habitat modifications for numerous aquatic organisms, including anadromous salmonids (Osmundson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Two-way ANOVA of %C indicated that differences based on stream were significant ðp50:001Þ; but differences based on reach within a given Table 4. Indicators of ecological integrity proposed by Wichert and Rapport (1998) and adapted by Shields et al, (2000) stream were not. Furthermore, a longitudinal trend was not evident for any stream (Figure 3).…”
Section: Resultsmentioning
confidence: 92%
“…Values for indicators for each fish species were gleaned from the literature as described by Shields et al, (2000). When different values occurred for the age at maturity for males and females, the average value was used in analysis.…”
Section: Methodsmentioning
confidence: 99%